Official Financing for Developing Countries. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2001)
This paper reports an updated assessment of movements in official financing for developing countries during 1997-1999. The composition of official financing flows changed too; as a result of the Asian crisis Member states of the Development Assistance Committee (DAC) increased official development financing from USD 73 billion in 1996 to USD 85 billion in 1999. At the same time, however, new commitments by export credit agencies-a resource not included in the DAC figures-declined during this period, reflecting a slowing down in large-scale projects as governments affected by the Asian financial crisis suspended or postponed a number of public sector projects. The debt relief and its orientation toward poverty reduction is an important contribution to international efforts to help raise the living standards of the poorest in the world. Its success, however, will crucially depend on the willingness of donor countries to increase resources for development aid and link them to the recipient countries' poverty reduction strategies.